Pelatihan Pembuatan Soal Berbasis HOTS Bagi Guru Mata Pelajaran Sejarah SMA di Kabupaten Karanganyar - Kurniawan, Dadan Adi; Sutiyah, Sutiyah; Djono, Djono; Purwanta, Hieronymus; Pelu, Musa; Isawati, Isawati; Herimanto, Herimanto; Suryani, Nunuk (DEDIKASI: Community Service Reports, 2023)
History is a subject that is often considered boring, especially by students at the high school (SMA) level, including high school in Karanganyar Regency, Central Java. Boredom is generally caused by much historical material, tends to be memorized, and the learning process is monotonous in terms of teachers' models, methods, techniques and questions. History questions are considered less varied because they often feature multiple-choice types and standard descriptions. As a result, students need to be more developed in optimizing their potential thinking power. For this reason, the UNS History Education Study Program initiated training in preparing HOTS (Higher Order Thinking Skills) questions as an essential provision for high school history teachers in Karanganyar. The method used is training, mentoring and assignment. Through this training, it was concluded that: First, history teachers must understand the meaning, purpose and importance of using HOTS-based questions in 21st-century history learning. Second, history teachers must understand various types of history questions such as essays, multiple choice, true-false, completion, short answer, and assignment. Third, history teachers must practice mastering the skills of compiling HOTS-based varied history questions. Fourth, implementing the HOTS-based varied history questions in daily high school history learning so that it becomes a habit.